OP06 5-aminosalicylates are not associated with adverse outcomes in Inflammatory Bowel Disease patients with COVID-19: Analysis from an international registry. (27th May 2021) - Ungaro, R; Brenner, E; Agrawal, M; Gearry, R B; Kaplan, G G; Kissous-Hunt, M; Ng, S C; Rahier, J F; Reinisch, W; Steinwurz, F; Zhang, X; Lewis, J D; et al.
Abstract: Background: Prior data have suggested that 5-aminosalicylates (5-ASA) may be associated with an increased risk of severe COVID-19 among inflammatory bowel disease (IBD) patients. We aimed to evaluate the association of 5-ASA with severe COVID-19 in a large cohort of IBD patients. Methods: We analyzed data from the Surveillance Epidemiology of Coronavirus Under Research Exclusion for Inflammatory Bowel Disease (SECURE-IBD) registry, a large, international database of IBD patients with confirmed COVID-19. The primary outcome was severe COVID-19, defined as intensive care unit admission, ventilator use, and/or death. Hospitalization due to COVID-19 was a secondary outcome. We performed multivariable regression modeling with a generalized estimating equation accounting for country as a random effect to analyze the association of 5-ASA with severe COVID-19. Models a priori included age, sex, race, disease phenotype (CD or UC/IBD-U), corticosteroid use, azathioprine/6-mercaptopurine use, TNF antagonist use, disease activity by physician global assessment, number of comorbidities, and days from SECURE-IBD inception to reporting. We constructed three models examining 5-ASA use as binary covariate using 1) all patients, 2) only patients on any biologic, and 3) only patients on TNF antagonists. Results: 5, 174 patients were included with 212 (4.1%) severe COVID-19 events. At the time of COVID-19 infection, 1, 504 patients were taking 5-ASA. 5-ASA patients were older (mean age 44 vs. 38.3 years, p<0.001), more likely to have UC (70.7% vs. 27.7%, p<0.001), less likely to be in remission (49.6% vs. 57.2%, p<0.001), and more likely to have at least one comorbidity (33.6% vs. 26.7%, p<0.001) compared to patients not on 5-ASA. 3, 325 patients were on any biologic and 2, 216 were on a TNF antagonist. Among all patients, 5-ASA was not associated with severe COVID-19 (adjusted OR [aOR] 1.14, 95% confidence interval [CI] 0.86–1.52) (Table 1). Prior associations of age, comorbidities, TNF antagonists, and corticosteroids with severe COVID-19 were similar to prior analyses (Table 1). In analyses restricting to those on any biologic or only TNF antagonists, there was also no significant association between 5-ASA and severe COVID-19 (aOR 0.76, 95% CI 0.38–1.50 and aOR 0.99, 95% CI 0.43–2.32, respectively). Use of 5-ASA was not associated with risk of COVID-19 related hospitalization in any analysis. Conclusion: In an analysis of updated data from the SECURE-IBD registry, 5-ASA use was not associated with worse outcomes among IBD patients with COVID-19.